Sonosensitizer‐Functionalized Graphene Nanoribbons for Adhesion Blocking and Sonodynamic Ablation of Ovarian Cancer Spheroids. Issue 13 (29th May 2021) - Lee, Hak Rae; Kim, Dae Woo; Jones, Victoria O.; Choi, Yunkyu; Ferry, Vivian E.; Geller, Melissa A.; Azarin, Samira M.
Abstract: Advanced stage ovarian cancer is challenging to treat due to widespread seeding of tumor spheroids throughout the mesothelial lining of the peritoneal cavity. In this work, a therapeutic strategy using graphene nanoribbons (GNR) functionalized with 4‐arm polyethylene glycol (PEG) and chlorin e6 (Ce6), a sonosensitizer, to target metastatic ovarian cancer spheroids is reported. GNR‐PEG‐Ce6 adsorbs onto the spheroids and disrupts their adhesion to extracellular matrix proteins or LP‐9 mesothelial cells. Furthermore, for spheroids that do adhere, GNR‐PEG‐Ce6 delays spheroid disaggregation and spreading as well as mesothelial clearance, key metastatic processes following adhesion. Owing to the sonodynamic effects of Ce6 and its localized delivery via the biomaterial, GNR‐PEG‐Ce6 can kill ovarian cancer spheroids adhered to LP‐9 cell monolayers when combined with mild ultrasound irradiation. The interaction with GNR‐PEG‐Ce6 also loosens cell–cell adhesions within the spheroids, rendering them more susceptible to treatment with the chemotherapeutic agents cisplatin and paclitaxel, which typically have difficulty in penetrating ovarian cancer spheroids. Thus, this material can facilitate effective chemotherapeutic and sonodynamic combination therapies. Finally, the adhesion inhibiting and sonodynamic effects of GNR‐PEG‐Ce6 are also validated with tumor spheroids derived from the ascites fluid of ovarian cancer patients, providing evidence of the translational potential of this biomaterial approach. Abstract : Graphene nanoribbons (GNR) functionalized with 4‐arm polyethylene glycol (PEG) and the sonosensitizer chlorin e6 (Ce6) associate with ovarian cancer spheroids and disrupt mesothelial adhesion of the spheroids. Combined with ultrasound irradiation, GNR‐PEG‐Ce6 kills ovarian cancer spheroids adhered to LP‐9 mesothelial cell monolayers via sonodynamic effects, suggesting that this approach can reduce ovarian cancer metastasis in the peritoneal cavity.